Pemanfaatan Teknologi AI untuk Tahqiq Kitab Makhthut: Digitalisasi Naskah Arab Klasik di Universitas Al-Wasatiya Hadramaut Yaman - Maslakha, Hidayatul; Hamdani, Muhammad; Mukarromah, Ngalimatul; Nafisa, El Saffa; Pramudita, Sinta (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study explores the use of Artificial Intelligence (AI) in the verification (tahqiq) of Arabic manuscripts, focusing on digitizing classical texts at Universitas Al-Wasatiya Hadramaut, Yemen. The tahqiq process, essential for final-year Ushul Fiqh students, involves transcribing and verifying handwritten manuscripts to preserve Islamic intellectual heritage. Challenges like unclear handwriting, complex terminology, and damaged manuscripts complicate this task. The research highlights AI tools, such as Google Image Search, to improve manuscript digitization efficiency and accuracy. AI aids in handwriting recognition and speeds up transcription, though manual oversight remains necessary for text authenticity. Using a qualitative case study, data were collected through interviews, document analysis, and observations. Findings show AI significantly supports tahqiq by reducing manual effort and speeding up transcription. However, technical issues, like errors in character recognition, emphasize the need for human expertise. Recommendations focus on integrating AI to modernize tahqiq while preserving cultural heritage.